2012
DOI: 10.1371/journal.pone.0037222
|View full text |Cite|
|
Sign up to set email alerts
|

Dihydroartemisinin Enhances Apo2L/TRAIL-Mediated Apoptosis in Pancreatic Cancer Cells via ROS-Mediated Up-Regulation of Death Receptor 5

Abstract: BackgroundDihydroartemisinin (DHA), a semi-synthetic derivative of artemisinin, has recently shown antitumor activity in various cancer cells. Apo2 ligand or tumor necrosis factor-related apoptosis-inducing ligand (Apo2L/TRAIL) is regarded as a promising anticancer agent, but chemoresistance affects its efficacy as a treatment strategy. Apoptosis induced by the combination of DHA and Apo2L/TRAIL has not been well documented, and the mechanisms involved remain unclear.Methodology/Principal FindingsHere, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 52 publications
2
41
1
Order By: Relevance
“…DHA also substantially reduced tumor development in nude mice xenografted with BxPC-3 (Kong et al, 2012). Concordant with similar approach, another study highlighted ROS/ERK/p53-mediated upregulation of death receptors in Gamma-tocotrienol treated Panc-1 and MiaPaca-2 cells (Kannappan et al, 2010).…”
Section: Molecular Basis Of Trail Resistancesupporting
confidence: 58%
“…DHA also substantially reduced tumor development in nude mice xenografted with BxPC-3 (Kong et al, 2012). Concordant with similar approach, another study highlighted ROS/ERK/p53-mediated upregulation of death receptors in Gamma-tocotrienol treated Panc-1 and MiaPaca-2 cells (Kannappan et al, 2010).…”
Section: Molecular Basis Of Trail Resistancesupporting
confidence: 58%
“…Apoptosis induced by DHA in different cancer cells has been reported [21][22][23][24][25][26][27][28][29][30]. In the present study, we examined apoptosis in human androgen-independent PC3 prostate cancer cells after DHA treatment, by flow cytometry and TEM.…”
Section: Discussionmentioning
confidence: 82%
“…Dihydroartemisinin (DHA), a semisynthetic derivative of artemisinin isolated from the Chinese medicinal plant Artemisia annua L., has been widely used as an effective antimalarial drug [15][16][17][18][19]. Recently, many studies have shown that DHA is the most potent anticancer agent among artemisinin and its derivatives [20], and has in vitro and in vivo anticancer activity in different types of human cancer cells, such as hepatocellular carcinoma, prostate cancer, gastric cancer, osteosarcoma, breast cancer, esophageal cancer, pancreatic cancer, lung cancer, and ovarian cancer [21][22][23][24][25][26][27][28][29][30][31]. It has been demonstrated that DHA can induce apoptosis and/or inhibit proliferation of cancer cells [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated cells served as controls. The amount of intracellular ROS was expressed as the fold-increase of DCF fluorescence compared with the control [16]. The experiments were repeated three times.…”
Section: Measurement Of Ros Generationmentioning
confidence: 99%